Treating TNF Receptor Associated Periodic Fever Syndrome in End-Stage Renal Failure - J. Coutinho; R. S. Chorão; M. Oliveira; C. R. Santos (Case Reports in Nephrology)
Tumor necrosis factor receptor associated periodic syndrome (TRAPS) is a rare monogenic autoinflammatory disease. Its most severe manifestation is secondary amyloidosis. A 44-year-old male presented with nephrotic syndrome. Kidney biopsy was conclusive for secondary amyloidosis. The patient and his children had a history of recurrent febrile periods since infancy. All subjects were positive for a heterozygous variant of the TNFRSF1A gene, confirming TRAPS diagnosis. The patient progressed to end-stage renal failure and developed recurrent pericarditis episodes. He was started on anakinra while on hemodialysis with marked reduction of his serum amyloid A protein (SAA) levels. Meanwhile he received a cadaveric renal transplant and maintains anakinra treatment. Despite renal failure being the most feared complication of AA amyloidosis caused by TRAPS, little data is available about safety of anti-IL-1 treatment in patients with severe kidney failure. The authors report this case of a patient on dialysis treated with anakinra in which no complications were registered. Though amyloidosis is established, the authors believe containing its progression and reducing inflammatory activity can improve patient prognosis and reduce recurrence of amyloidosis in kidney transplant, as has been demonstrated in transplanted patients due to familial Mediterranean fever amyloidosis.